Al-Kindy College Medical Journal: Benchmarks to Streamline the Desk’s Workflow and Harvest New Milestones - Al-Mendalawi, Mahmood D. (AL-Kindy College Medical Journal, 2026)
This editorial outlines key strategic benchmarks to enhance editorial workflow, publication quality, journal visibility, and scientific impact.